Parents' perceptions of driver education: A theoretically guided qualitative investigation. (February 2021) - Rodwell, David; Alexander, Marina; Bates, Lyndel; Larue, Grégoire S.; Watson, Barry
Highlights: Goals for Driver Education (GDE) was applied to Parent-supervised practice driving. Parents are likely to outsource learning activities at the lower GDE levels. Parents concerned about 'knowledge gaps' and avoiding conflicts with their child. Parents would welcome specific parent-focused training on driver supervision. Abstract: In many jurisdictions with Graduated Driver Licensing systems, such as those in North America, Australia, and New Zealand, parents play an important role in teaching their child how to drive and facilitating their access to formal driver education. This study explored parents' views on these processes in a theoretically grounded manner using the Goals for Driver Education (GDE) Framework. The GDE framework groups influences on young driver behaviour into four interconnected hierarchical levels: vehicle manoeuvring (Level 1), mastery of traffic situations (Level 2), goals and contexts for driving (Level 3) and goals for life and skills for living (Level 4). Fourteen parents of novice drivers participated in five focus groups held in urban and regional locations in South East Queensland, Australia. A six-step thematic analysis was used consisting of (1) familiarisation with the data, (2) generation of initial codes, (3) searching for themes, (4) reviewing themes, (5) defining and naming themes and (6) producing the report. Parents indicated that they were more likely to outsource the teaching of skills at Levels 1 and 2 of the GDE to professional driving instructors as they were concerned that they would pass bad habits onto their child or they were unaware of the road rules that their child was required to follow. Parents believed that they were able to more effectively teach skills located on Levels 3 and 4 of the GDE framework because they had a greater knowledge of their child when compared with professional educators. The study findings can be used to develop an intervention that would support parents to more effectively supervise learner drivers.